Commercialization of Fishery and Aquaculture Products in India-Problems and Solutions - Sawant, Bhawesh T.; Sawant, Paramita Banerjee (Indian Journal of Marketing, 2011)
The Indian market in fish products is being diversified in terms of fresh, frozen and value added products. Revolution in domestic retail sector has enabled value added food products to enter global competitive markets. However, distribution and marketing system of fish products is still in a very nascent stage. Hence, there is an urgent need to commercialize and market fish products with skilful publicity, sales promotion and marketing. The present paper attempts to discuss about and bring this relevant issue into the limelight, with examples of how skilful advertising and sales promotion has enhanced marketability of products.